Using OpenMP: Portable Shared Memory Parallel Programming : Barbara Chapman, Gabriele Jost, Ruud van der Pas The MIT Press, 2008 - Tinetti, Fernando Gustavo (2010)
The book Using OpenMP: Portable Shared Memory Parallel Programming, presents OpenMP more than appropriately, from the perspective of high performance computing, which traditionally has provided most (if not all) the parallel software development strategies.